Sinestesia: projeto editorial de suplemento para o periódico Dito Efeito - Baldini, Adriane (2023)
The objective of this dissertation is to present and develop the editorial project of the magazine Sinestesia as a proposal for the supplementary publication of the periodical Dito Efeito, maintained by the Department of Language and Communication (DALIC) of the Universidade Tecnológica Federal do Paraná (UTFPR), campus Curitiba. The purpose is to add to Dito Efeito magazine a publication that conveys texts that present a more essayistic and free approach to themes related to the academic and scientific universe, seeking to expand the readership and the number of collaborators. The project also aims to promote a broader dialogue between disciplines whose object is discussions around different languages. The research will be conducted through the qualitative method, using the dialectical and bibliographical methodology. The main theorists that will be referenced in the study are Braida e Nojima (2014), Kellner (2001), Matsushita (2021), Meadows (1998) and Scalzo (2004).